(untitled) (Archives of Criminology, 2023)
Electronic monitoring (EM) is a fixture in most criminal justice systems in Europe and around the world, but there is limited research on how EM operates in Eastern European states. Previous comparative research identified two distinct approaches to how EM is used and operated but Eastern Europe was not included in the analysis (Hucklesby, Beyens, Boone 2021). This paper addresses this knowledge gap by examining the use of EM in Poland and comparing it with England and Wales, thereby identifying similarities and differences in their approaches. The two jurisdictions are good comparators because the Polish system was originally modelled on England and Wales, they were both early adopters of EM in their respective parts of Europe, they share common problems of high prison populations and overcrowded prisons and they use EM extensively. The paper explores whether Poland has a distinct approach to EM implementation which differs from the British or Western European approaches and whether there might be a distinctive Eastern European model of EM. It argues that whilst the Polish approach to EM has evolved away from the British approach to share many of the features of the Western European model, it is sufficiently distinctive to suggest the existence of a third model or approach. Consequently, it raises questions about whether there is an Eastern European model or whether Poland’s approach is unique. The paper concludes by examining enduring questions about whether the approach of England and Wales or Poland have more effectively managed prison populations. It suggests that EM’s impact on prison populations has been marginal at best in both jurisdictions, putting ethical issues about its use into sharper focus.